2014
DOI: 10.1080/07373937.2013.835318
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Quality Characteristics of Infrared Radiation–Dried Kelp at Different Peak Wavelengths

Abstract: Drying experiments on kelp (seaweed species) were conducted using air drying (AD) and infrared radiation drying (IRD) at different emission peak wavelengths of 2.4, 3.0, 5.0, and 6 0 m. Temperature characteristics of the dried kelp were determined in terms of temperature distribution and surfaceinterior temperature variation. Rehydrated ratio, color, and texture before and after rehydration were measured to evaluate the quality of dried kelp products. Dielectric properties were also studied to observe the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 43 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…[27] The samples were compressed in two consecutive cycles of 50% compression, with an interval of 5 s between the two cycles, using a plane probe 2 mm in diameter (SMS-P=2, Stable Micro Systems, Ltd., Surrey, UK). Average values of texture characteristics from eight measurements were calculated for each experimental condition.…”
Section: Texture Analysismentioning
confidence: 99%
“…[27] The samples were compressed in two consecutive cycles of 50% compression, with an interval of 5 s between the two cycles, using a plane probe 2 mm in diameter (SMS-P=2, Stable Micro Systems, Ltd., Surrey, UK). Average values of texture characteristics from eight measurements were calculated for each experimental condition.…”
Section: Texture Analysismentioning
confidence: 99%
“…5. Xu et al (2014) showed that dried kelp samples using IR-assisted hot-air drying were found to have better fresh-like quality and higher rehydration ratio compared to the air-dried samples. [142] It was reported that the application of IR-assisted hot-air drying produced betterquality carrot slices in terms of Vitamin C (54%) and absorbed more water during rehydration.…”
Section: Infrared (Ir)-assisted Dryingmentioning
confidence: 97%
“…Xu et al (2014) showed that dried kelp samples using IR-assisted hot-air drying were found to have better fresh-like quality and higher rehydration ratio compared to the air-dried samples. [142] It was reported that the application of IR-assisted hot-air drying produced betterquality carrot slices in terms of Vitamin C (54%) and absorbed more water during rehydration. [143] The quality of red bell pepper products dried using microwave and infrared-hybrid convective drying was much better than those dried using convective drying and the energy consumption was minimized due to short drying time.…”
Section: Infrared (Ir)-assisted Dryingmentioning
confidence: 97%
“…Xu et al . () studied drying of kelp using IR radiation. It was found that the total drying time required for IR drying products was approximately 120 min, reduced by 56% compared to air drying.…”
Section: Ir Radiation Heating In Different Dryersmentioning
confidence: 99%
“…A combination of a low-intensity IR radiation (2000 W/m 2 ), inlet air temperature (30C) and moderate values of inlet air velocity (0.15 m/s) was found to effectively improve the final quality of paddy. Xu et al (2014) studied drying of kelp using IR radiation. It was found that the total drying time required for IR drying products was approximately 120 min, reduced by 56% compared to air drying.…”
Section: Ir-assisted Hot Air Dryingmentioning
confidence: 99%